Microbial biotransformation of male specific pheromone α-copaene with cunninghamella elegans and antibacterial activity of its transformed products / Syed Adnan Ali Shah ... [et al.] - Ali Shah, Syed Adnan; Atif, Muhammad; Sultan, Sadia; Erum, Saira; Hussain, Samreen (Faculty of Pharmacy, 2023)
Pharmaceutical industries are increasingly turning to microbial transformation instead of chemical methods. This is because microbial biotransformation is a more effective way to produce pharmacologically active molecules with high specificity and efficient yield. Additionally, it is a step towards eco-friendly synthesis. α-Copaene (1), a tricyclic sesquiterpene, is a potent attractant of the male Mediterranean fruit fly Ceratitis capitata. This paper presents the utilization of the filamentous fungus Cunninghamella elegans TSY 0865 for large-scale biotransformation of 1. α-Copaene (1) has been incubated with Cunninghamella elegans for 11 days and extracted with CH 2 Cl 2 . Four new hydroxylated metabolites 10,13-dihydroxycopaene (2); 11,13-dihydroxycopaene (3); 11-hydroxycopaen-5-one (4); and 11-hydroxy-13-copaenic acid (5) were afforded. The structures of the new metabolites were elucidated by 1D ( 1 H, 13 C) and 2D NMR (COSY, HMBC, HMQC, and NOESY) techniques and MS analyses. Metabolite 5 exhibited significant antibacterial activity against Bacillus subtilis and Pseudomonas aeruginosa.